MENINGKATKAN HASIL BELAJAR BERKREASI SENI RUPA DENGAN MENGGUNAKAN METODE EKSPERIMEN SISWA KELAS VII A SMP NEGERI 24 KABUPATEN TEBO - BENGET P. NAINGGOLAN, Drs. Erfahmi, M.Sn, Drs. Mediagus (Serupa The Journal of Art Education, 2013)
One way to improve student achievement in creative learning activities art is the use of experimental methods. This study aims to determine the extent to which improving student achievement in the creative arts after using experimentalmethods in learning activities. The subjects were students of class VII A SMP Negeri 24 Kabupaten Tebo in Academic Year 2012/2013. This research is a class action research (CAR), and performed in 2 cycles. The results showed an increase in student achievement. Improved achievement is evident from the increased experimental methods learning activity such as following the process, his own experience, experimenting, observing the process and results, gain the experienceto experiment, carry out the work according to the procedures and collect assignments on time. Improved achievement can be seen from the mastery of achievement increased from an average of 55% in cycle 1 increased to 100% in cycle 2. This increase can not be separated from the students' understanding of learning materials and implement the learning process with the experimental method. It can be concluded that the experimental method of learning canimprove student learning activities and thus can improve student achievement. Key words : Achievement, Experimental Method.